Ireland’s fallow deer: their historical, archaeological and biomolecular records - Beglane, Fiona; Baker, Karis; Carden, Ruth; Hoelzel, A. Rus; Lamb, Angela L.; Fhionnghaile, Rita Mhig; Miller, Holly; Sykes, Naomi (Royal Irish Academy, 2018)
The Anglo-Normans first introduced fallow deer (Dama dama) to Ireland in the thirteenth century, however no biomolecular research has previously been undertaken to examine the timing, circumstances and impact of the arrival of this species. This study combines historical, zooarchaeological, genetic and iso-topic data from both medieval and post-medieval samples to address this lack of research. The paper identifies a peak in the presence of fallow deer in Ireland between the thirteenth and fourteenth centuries, with a corresponding peak in documentary evidence for their presence in the thirteenth century. The deer are predominantly male, and from castle sites, supporting the historical evidence for their link with elite hunting. The English origin of the source populations shows correspondence between the documentary evidence, suggesting a western bias—and genetic evidence—with a similarity to southern and western England. Furthermore a stable isotope study identifies two possible first-generation imports, one dating from the medieval period and one from the post-medieval period.